Association of patient age with first pass success in out-of-hospital advanced airway management. (August 2019) - Jarvis, Jeffrey L.; Wampler, David; Wang, Henry E.
Abstract: Background: First pass advanced airway insertion success is associated with fewer adverse events. We sought to compare out-of-hospital endotracheal intubation (ETI) and supraglottic airway (SGA) first-pass success (FPS) rates between adults and children in a national cohort of EMS agencies. Methods: We analyzed data from 2017 using a national cohort of 731 EMS agencies. Using multivariable logistic regression, we compared the odds of ETI and SGA FPS between adult (age >14 years) and pediatric (age ≤ 14 years) patients, adjusting for gender, ethnicity, indication, and drug facilitation. We performed a sensitivity analysis of all patients using age as a continuous variable for both ETI and SGA FPS. Finally, we calculated the odds of FPS using all possible age break points between 10 and 18 years old. Results: A total of 29, 368 patients (28, 846 adults and 522 children) received ETI (22, 519) or SGA (6849). ETI FPS was higher in adults than children; 72.7% vs, 58.5%, (OR 1.80, 95% CI 1.49–2.17). SGA FPS was similar between adults and children; 89.8% vs 84.6%, (OR 1.63, CI 0.70–3.31). When analyzed as a continuous variable, ETI FPS remained associated with age in years: OR 1.007 (CI 1.006–1.009) and SGA FPS showed no significant association with age: OR 0.999 (0.995–1.004). The OR for ETI FPS were higher in adults than pediatrics at all potential age break points between 10 and 18 years old. The OR for SGA FPS was significantly more likely in adults than pediatrics using 16 as a break point but not significantly different between adults and pediatrics using any other age break point. Conclusion: In this national cohort of out-of-hospital patients, ETI FPS was higher for adults than children. SGA FPS did not significantly vary with age. SGA FPS was higher than ETI FPS at all ages.